Desain Dan Pengembangan E-Learning Dengan Manajemen Pengguna Menggunakan Konsep UI/UX - Jonathan, Jeremy; Rahdiana, Ikhsan; Baldy Imalian, Muhhamad (Jurnal Teknik Informatika, 2025)
In the current digital era, information and communication technology plays a crucial role in education, one of which is through e-learning which offers flexibility and broad access for students and teachers. This research aims to design and develop an e-learning website that is equipped with user management and book purchase features using HTML, CSS, JavaScript, PHP technology, as well as applying good UI/UX concepts. This website is designed to facilitate an interactive and efficient online learning process, as well as providing a platform for purchasing learning support books. The development method used is a user-centered design approach with stages of needs analysis, design, implementation and testing. The result of this research is an e-learning website that is responsive, easy to use, and has an attractive interface. The user management feature allows administrators to manage user data, while the book purchase feature is integrated to make it easier for users to obtain additional learning materials. Functionality and usability testing shows that the website functions well and meets user needs. Thus, this website can be an effective solution to support online learning activities and integrated book purchase transactions.